Protected cultivation can mitigate carbon emissions for tomato production - Hairong Gao; Shaokai Wang; Dandan Shen; Wenshuang Li; Yan Zhang; Jingyi Deng; Jiapeng Jiao; Pinge Huang; Qianli Ma; Yuan Huang; Fangting Yuan; Xin Wang; et al. (Agriculture Communications)
Summary: Protected cultivation enables the production of vegetables and fruits throughout the year without compromising of farming field for grain production. However, it is generally associated with high resource consumption, including building materials, consumables, and energy, raising severe concerns about its future sustainability, especially the intensity of its carbon emissions, which is less well-understood. This study focused on the carbon emissions of two typical protected cultivation constructions for tomato cultivation in China, using life cycle assessment (LCA). Tomato production generated 354.4 and 173.1 kg CO2-eq/ton carbon emissions in a typical solar greenhouse in northern China and a typical naturally ventilated polyhouse in southern China, which represented 41.9% and 21.7% reduction, respectively, compared to field production in the same area. Further analysis of protected cultivation inputs revealed that agricultural consumables are the main contributors to carbon emissions. Among them, fertilizers were the dominant contributor to carbon emissions, accounting for 73.0% and 67.5% of the total carbon emissions for solar greenhouses and polyhouses, respectively. Based on this finding, a sensitivity analysis revealed the potential of two advanced fertilizer management practices to reduce carbon emissions. Drip irrigation and slow-release fertilizers in protected cultivation can reduce carbon emissions by 16.5–17.7% and 12.9–13.8%, respectively, compared to traditional chemical fertilizers. In addition, the analysis of environmental effects suggested that protected tomato production can significantly reduce environmental impact. Overall, this research highlighted that protected cultivation can substantially mitigate carbon emissions, demonstrating its high efficiency toward low-carbon agriculture.